Gamblang (Steel and Brilliant Mental Generation) as an Effort to Improve Mental Health of School-Based Adolescents at SMK Negeri III Tahuna - Tooy, Gracia Christy; Bajak, Chatrina Maria Agustina; Umboh, Melanthon Junaedi; Patras, Mareike Doherty; Tatangindatu, Maryati Agustina; Wuaten, Grace Angel (Abdimas Indonesian Journal, 2025)
The Sangihe Islands Regency is an outermost Indonesian archipelago with a significant number of adolescents and faces serious challenges related to adolescent mental health. One prominent case was a suicide attempt by a student at SMK Negeri 3 Tahuna due to depression, reflecting the importance of psychosocial interventions in the school environment. The "GAMBLANG" Community Service Program (PMUP) was implemented as a promotional and preventive effort to increase students' knowledge and awareness of mental health. Activities included counseling, pre-post tests, and early detection of mental health using the LiveWell by Zurich application. The analysis showed a significant increase in student knowledge (p < 0.05) after the counseling, and 1 in 12 students showed signs of a real mental disorder. This program was also followed by the provision of a first aid kit to support the establishment of a school health center (UKS). The GAMBLANG program is expected to become an effective school-based intervention model in increasing the mental resilience of adolescents in border areas.